스퍼터링 타겟 적용을 위한 방전플라즈마 소결공법으로 소결된 Cu의 특성평가 - 장준호; Jun Ho Jang; 박현국; Hyun Kuk Park; 우기도; Kee Do Woo; 남효은; Hyo Eun Nam; 오익현; Ik Hyun Oh (대한금속·재료학회지, 54(1), 2016)
Pure Cu compacts were fabricated by spark plasma sintering (SPS) process for sputtering target application. For the fabrication of the Cu compacts, conditions such as temperature, pulse ratio, pressure, and heating rate were optimized during the sintering process. The final sintering temperature required to fabricate the target materials with high density, and the heating rate up to the final temperature, were 800 °C and 80 ℃/min, respectively. The heating directly progressed to 800 °C without any holding time. Sputtering target materials with high relative density of 99.7% were fabricated in a uniaxial pressure range of 60 MPa at a sintering temperature of 800 °C, without any significant change in the grain size. Also, the shrinkage displacement of the Cu target materials was found to considerably increase with increasing pressure at sintering temperatures up to 800 °C.